Evaluation of innovative management success criteria in hotel establishments: Case study in Giresun-Turkey - Demirdağ, Şerif Ahmet; Korucuk, Selçuk; Karamaşa, Çağlar (Decision Making: Applications in Management and Engineering, 2021)
The purpose of this study was to determine the success criteria for innovative management in hotel establishments that have a corporate identity in the Turkish city of Giresun as well as to find out the best hotel by ranking them based on the determined criteria. For the study, “Multi-objective Optimization by Simple Ratio Analysis (MOOSRA)” and “Evaluation Based on Distance from Average Solution (EDAS)” methods were used. The results revealed that the success criteria for innovative management are beneficial in increasing operational efficiency, performance, and customer satisfaction. The results also show that managers are well aware of the success criteria for innovative management that should be prioritized, as well as those that are likely to lead to the success of their establishments and keep them ahead of the competition. While “Presenting an Innovative Vision” was found as the most important success criteria, “Use of In-Hotel Information Sources” came out as the least important one. The hotels considered were then ranked following the identified criteria.